Islamic Education Institute for Children of Madurese Migrant Workers in Malaysia - Ulil Firdausiyah; Muhammad Ihsan; Maimun, Maimun (al-Afkar, Journal For Islamic Studies, 2025)
This article examines the existence and role of Islamic educational institutions for the children of migrant workers from Madura in Malaysia. The phenomenon of labour migration from Indonesia to Malaysia has created a need for adequate education for the children of migrant workers, especially in the context of Islamic education which is an integral part of their cultural identity. This research uses a qualitative method with a case study approach, involving in-depth interviews and field observations in several Madurese communities in Malaysia. The research results show that there are various Islamic educational institutions that serve the children of Madurese migrant workers, ranging from formal institutions such as the Kota Kinabalu Indonesian School (SIKK) and the Kuala Lumpur Indonesian School (SIKL), to non-formal institutions such as the Indonesian Education Center (PPI) and Madurese Learning Community (KBM). Apart from that, there are also informal educational initiatives such as home recitations and study programs at mosques or surau. While these institutions play a key role in defending Islamic values and Madurese culture, they face various challenges such as resource constraints, legality issues, and the need to balance religious education with the demands of general education. This article also explores the adaptation strategies implemented by these institutions, including the use of technology for distance education and cooperation with local authorities. In conclusion, the existence of Islamic educational institutions for the children of Madurese migrant workers in Malaysia has deep significance, not only in the context of religious education, but also as a means of cultural preservation and preparation for reintegration into Indonesia. This research recommends increased support from the governments of Indonesia and Malaysia, as well as closer cooperation between various stakeholders to strengthen and develop these Islamic educational institutions.